1985
DOI: 10.1038/318470a0
|View full text |Cite
|
Sign up to set email alerts
|

Human blood platelets showing no response to collagen fail to express surface glycoprotein Ia

Abstract: The interaction of blood platelets with collagen is generally considered to be of primary importance in the arrest of bleeding and to have a role in the pathogenesis of thrombosis and atherosclerosis. Following damage to the vascular endothelium, circulating platelets come into contact with exposed collagen fibrils in the subendothelium and spread along it; this is followed by the secretion of several biologically active substances and by aggregation of platelets. The glycoproteins of the platelet plasma membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
241
2
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(248 citation statements)
references
References 17 publications
4
241
2
1
Order By: Relevance
“…Platelets express two receptors for this matrix component: integrin ␣ 2 ␤ 1 and glycoprotein VI (2). Integrin ␣ 2 ␤ 1 is a good candidate for antithrombotic therapy because its overexpression is associated with stroke and myocardial infarction (3) and its underexpression results in a mildly prolonged bleeding time, which is quite different from the profound bleeding disorder observed in deficiency of the platelet fibrinogen receptor integrin ␣ IIb ␤ 3 (Glanzmann's thrombasthenia) (4)(5)(6)(7). However, previous studies on integrin ␣ 2 ␤ 1 inhibition (including monoclonal antibodies against ␣ 2 and murine knockout models) have been controversial, demonstrating equivocal results on the role of the integrin (8).…”
mentioning
confidence: 93%
“…Platelets express two receptors for this matrix component: integrin ␣ 2 ␤ 1 and glycoprotein VI (2). Integrin ␣ 2 ␤ 1 is a good candidate for antithrombotic therapy because its overexpression is associated with stroke and myocardial infarction (3) and its underexpression results in a mildly prolonged bleeding time, which is quite different from the profound bleeding disorder observed in deficiency of the platelet fibrinogen receptor integrin ␣ IIb ␤ 3 (Glanzmann's thrombasthenia) (4)(5)(6)(7). However, previous studies on integrin ␣ 2 ␤ 1 inhibition (including monoclonal antibodies against ␣ 2 and murine knockout models) have been controversial, demonstrating equivocal results on the role of the integrin (8).…”
mentioning
confidence: 93%
“…Postulated collagen receptors on the platelet surface include membrane glycoprotein (GP) Ia/IIa (integrin ␣ 2 ␤ 1 ) [1][2][3][4], GPIV (CD36) [5], GPVI [6,7], 85-90 kDa glycoprotein [8], and C1q receptor [9]. Recent studies have revealed that, among these proteins, GPIa/IIa and GPVI would have a physiological significance as collagen receptors on platelets [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that, among these proteins, GPIa/IIa and GPVI would have a physiological significance as collagen receptors on platelets [10,11]. Patients with a deficiency of GPIa/IIa or GPVI show a defective platelet response to collagen [1,2,7,[12][13][14], and antibodies against either glycoprotein inhibit platelet interaction with collagen [4,6,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the experimental data reported to date have been conflicting and have failed to support this model or to demonstrate clear and sufficient roles for ␣2␤1 and GPVI. Human ␣2␤1 deficiency states reportedly result in bleeding disorders and platelets with severely reduced collagen responses (9,10), but a recent analysis of mice lacking platelet ␣2␤1 demonstrated normal bleeding times, normal platelet adhesion to collagen, and almost no loss of platelet signaling responses to collagen (11). Deficiency of GPVI and its signaling partner Fc R␥, however, results in loss of platelet collagen responses in both human and mouse platelets (11)(12)(13).…”
mentioning
confidence: 99%